FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP DAYA INOVASI MASYARAKAT INDONESIA - Sobarsa , (Media Riset Bisnis & Manajemen, 2011)
The purpose of this paper is to report the result of a study aimed at the factors effect on innovation in Indonesia. Indonesia has many resources occupied by more than 300 etnics dispersed in 17,508 islands. It consists of a mixed population of Muslims, Hindus, Buddhist, Christians, and animists, which has created many kinds of cultural. These may have effect to their innovation. Data were collected from electronical and automotive industries situated in Jabotabek. These cities is a centre of activities of manufacturing industries that may reflect the industries throughout Indonesia. These industries is also deemed as full of innovation which might be effected by indonesian cultural. Factor analysis were used to determine the factors effect to the innovation. 150 quesionnaires were dispersed to managers of the firms and 127 of them were returned. The result of the study reveals that religion's values, cultural values, and education effect to the innovation. But, these factors indicate weak effect to Indonesian innovation. This is because of relaxed working, by pass, lack of leader figure, less national identity, perfunctorily, poor competitive power, and education manner are the factors efect to the innovation weaknesses. The study based on the data collected within automotive and electronical industries might be less representative to reveal the factors of Indonesian innovation. Additionally, the data collected might be small in number to make a general conclussion, while heteroginity of Indonesian cultural may also be handicap to the research conducted. This study has contributed to the efforts of revealing the ability of Indonesian innovation and its developement.Keywords : Innovation, Religion, Cultural, Education, Factor analysis